2020
DOI: 10.1096/fba.2020-00012
|View full text |Cite
|
Sign up to set email alerts
|

Pendrin stimulates a chloride absorption pathway to increase CFTR‐mediated chloride secretion from Cystic Fibrosis airway epithelia

Abstract: Cystic Fibrosis (CF), an inherited multi‐system disease, is caused by mutations in the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) that disrupt its ability to secrete anions from epithelia. Recovery of functional anion secretion may be curative for CF, so different components of the ion transport machinery have become attractive therapeutic targets. Several members of the SLC26 ion transporter family have been linked to epithelial ion flux, some through putative functional interactions with CFTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Organoid swelling was partly attenuated with the Na(+)-K(+)-Cl(−) cotransporter (NKCC1) inhibitor bumetanide, demonstrating Cl − dependence of forskolin-induced organoid fluid secretion ( Fig S2E and F ). Lack of complete inhibition may be explained by reabsorption and recycling of luminal-secreted Cl − or an ion channel–independent mechanism underlying fluid secretion caused by mechanical forces ( Bajko et al, 2020 ; Buddington et al, 2021 ). Moreover, chemical CFTR inhibitors significantly reduced FIS in HC NAOs ( Fig S2G and H ), indicating CFTR dependence.…”
Section: Resultsmentioning
confidence: 99%
“…Organoid swelling was partly attenuated with the Na(+)-K(+)-Cl(−) cotransporter (NKCC1) inhibitor bumetanide, demonstrating Cl − dependence of forskolin-induced organoid fluid secretion ( Fig S2E and F ). Lack of complete inhibition may be explained by reabsorption and recycling of luminal-secreted Cl − or an ion channel–independent mechanism underlying fluid secretion caused by mechanical forces ( Bajko et al, 2020 ; Buddington et al, 2021 ). Moreover, chemical CFTR inhibitors significantly reduced FIS in HC NAOs ( Fig S2G and H ), indicating CFTR dependence.…”
Section: Resultsmentioning
confidence: 99%
“…IL-4 and IL-13 activate SLC26A4 and CFTR in CF airway epithelial cells [87]. In addition, IL-4/IL-13-induced CFTR activation is attenuated by treatment with SLC26A4 inhibitor niflumic acid [87].…”
Section: Relationship Between Slc26a4 and Other Ion Transportersmentioning
confidence: 99%
“…Indeed upregulation of pendrin transcription has been shown in chronic rhinosinusitis and in rodent models of inflammatory lung diseases [ 125 , 126 , 127 ]. More recently, Bajko et al [ 128 ] showed that stimulation with interleukins IL-4, IL-13, or IL-17a increased pendrin levels in human bronchial epithelial cells from CF patients (CF HBECs) and non-CF donors (HBECs) [ 121 , 129 ]. Indeed, modulation of pendrin expression/activity by inflammation may represent a protective mechanism for re-alkalinization of ASL and epithelium defense during disease.…”
Section: Bicarbonate Transport In Airway Cellsmentioning
confidence: 99%